PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SUBSEKTOR FARMASI YANG TERDAFTAR DI BEI - Khofifah, Cindy; Susilowati, Dwi; Moorcy, Nadi Hermadi (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2025)
The purpose of this study is to find out the influence of Current Ratio, Debt to Equity Ratio, Total Asset Turnover and Net Profit Margin both simultaneously and partially to Profit Growth. The data used is existing sources, both internal and external data, and the data can be accessed through the internet and information publications. The data used is the financial statements of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The data analysis method uses multiple linear regression The results of the analysis show that the variable Current Ratio have a positive and significant effect on Profit Growth, Debt to Equity Ratio have a negative and insignificant effect on Profit Growth, Total Asset Turnover have a negative and significant effect on profit growth, Net Profit Margin have a negative and insignificant effect on Profit Growth.